Targeting the undruggable oncogenic KRAS: the dawn of hope - Hande Asimgil; Utku Ertetik; Nedim Can Çevik; Menar Ekizce; Alper Doğruöz; Muazzez Gökalp; Elif Arık-Sever; Rouzanna Istvanffy; Helmut Friess; Güralp Onur Ceyhan; Ihsan Ekin Demir (JCI Insight, 2022)
KRAS mutations are the drivers of various cancers, including non–small cell lung cancer, colon cancer, and pancreatic cancer. Over the last 30 years, immense efforts have been made to inhibit KRAS mutants and oncogenic KRAS signaling using inhibitors. Recently, specific targeting of KRAS mutants with small molecules revived the hopes for successful therapies for lung, pancreatic, and colorectal cancer patients. Moreover, advances in gene editing, protein engineering, and drug delivery formulations have revolutionized cancer therapy regimens. New therapies aim to improve immune surveillance and enhance antitumor immunity by precisely targeting cancer cells harboring oncogenic KRAS. Here, we review recent KRAS-targeting strategies, their therapeutic potential, and remaining challenges to overcome. We also highlight the potential synergistic effects of various combinatorial therapies in preclinical and clinical trials.